Fun classroom fitness routine ages 4 to 9 - Fink, Doug; Johns, Chris; Human Kinetics (Organization) (Illinois : Human Kinetics, 2008)
The DVD contains five ready-to-go fitness routines lasting 10 minutes each, plus a 7-minute warm-up and stretch routine. Each routine requires minimal prep time, and teachers can vary the routines to keep kids interested and having fun.'--Container
Title from title screen
Camera operator, Claude Barnes, Don Purger ; sound mixer, Don Grundsten ; graphic design, Scott Cimarusti
Host: Carol Scaini
Keywords: Physical education and training; Physical fitness for children; Physical fitness